English Lecturers' Ways in Assessing Students' Speaking Skill - Netta, Ayuna (Lembaga Penelitian, Penerbitan, Pengabdian dan Pengembangan Masyarakat (LP4M) Unmuha, 2021)
This study analyzes the lecturers ways in assessing students speaking skill. The study used a qualitative method to investigate four English lecturers and uses interview as the instrument to obtain the data needed. The findings show that the assessments used can be both formative and summative. The lecturers have utilized both formal and informal assessments to track and quantify their students' learning progress and determine whether the courses objectives have been met.